Metabolomic analysis of circulating tumor cells derived liver metastasis of colorectal cancer. Issue 1 (January 2023) - Li, Meng; Wu, Shengming; Zhuang, Chengle; Shi, Chenzhang; Gu, Lei; Wang, Peng; Guo, Fangfang; Wang, Yilong; Liu, Zhongchen
Abstract: Metabolic reprogramming is one of the essential features of tumor that may dramatically contribute to metastasis and collapse. The metabolic profiling is investigated on the patient derived tissue and cancer cell line derived mouse metastasis xenograft. As well-recognized "seeds" for remote metastasis of tumor, role of circulating tumor cells (CTCs) in the study of metabolic reprogramming feature of tumor is yet to be elucidated. More specifically, whether there is difference of metabolic features of liver metastasis in colorectal cancer (CRC) derived from either CTCs or cancer cell line is still unknown. In this study, comprehensive untargeted metabolomics was performed using high performance liquid chromatography-mass spectrometry (HPLC-MS) in liver metastasis tissues from CT26 cells and CTCs derived mouse models. We identified 288 differential metabolites associated with the pathways such as one carbon pool by folate, folate biosynthesis and histidine metabolism through bioinformation analysis. Multiple gene expression was upregulated in the CTCs derived liver metastasis, specifically some specific enzymes. These results indicated that the metabolite phenotype and corresponding gene expression in the CTCs derived liver metastasis tissues was different from the parental CT26 cells, displaying a specific up-regulation of mRNAs involved in the above metabolism-related pathways. The metabolic profile of CTCs was characterized on the liver metastatic process in colorectal cancer. The invasion ability and chemo drug tolerance of the CTCs derived tumor and metastasis was found to be overwhelming higher than cell line derived counterpart. Identification of the differential metabolites will lead to a better understanding of the hallmarks of the cancer progression and metastasis, which may suggest potential attractive target for treating metastatic CRC. Graphical abstract: Image 1 Abstract : Circulating tumor cell; Metabolomics; Colorectal cancer; Liver metastasis; Mouse models. Highlights: CTCs exhibit stronger invasion ability through metabolic reprogramming and EMT process. Liver metastases samples from CTCs derived CRC mouse were detected using HPLC-MS platform. Results of metabolomic analysis and pathway enrichment analysis both indicated that CTCs changed metabolic pathways during liver metastasis, including one carbon pool by folate, folate biosynthesis, histidine metabolism and other pathways.